Reforms of Notary Position Regulations in Indonesia Regarding Challenges and Opportunities in the Modernization Era - Maniah Maniah; Erniyanti Erniyanti (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
The notary profession in Indonesia is experiencing a critical transformation driven by technological advancements, changing legal landscapes, and the imperative of modernization. This research comprehensively examines the current regulatory framework governing notaries, analyzing the multifaceted challenges and potential opportunities for substantive reform in the contemporary legal ecosystem.The study employs a mixed-method approach, integrating qualitative legal analysis, comparative research, and empirical investigation to provide a holistic understanding of the notary profession's evolving role. Through in-depth examination of existing regulations, stakeholder interviews, and comparative international perspectives, the research identifies key systemic barriers and innovative pathways for professional development.Critical findings reveal significant challenges, including technological adaptation gaps, regulatory inflexibility, and inconsistent professional standards. The research highlights the urgent need for a dynamic regulatory approach that balances traditional legal principles with emerging digital authentication technologies. Key opportunities emerge in areas such as blockchain-based document verification, comprehensive digital skills training, and adaptive professional development frameworks.The study proposes a comprehensive reformation strategy encompassing technological infrastructure development, professional skills enhancement, and regulatory modernization. Recommendations include establishing dedicated innovation units, implementing mandatory technology training programs, and creating flexible regulatory mechanisms that can rapidly respond to technological and professional landscape changes. By providing a nuanced analysis of the notary profession's current state and future potential, this research contributes critical insights to the discourse on legal professional modernization in Indonesia. The findings underscore the essential role of strategic, forward-looking reforms in ensuring the continued relevance, effectiveness, and integrity of notarial services in the digital era.